Effects of hydrogen fraction in co-injection gas on combustion characteristics of the raceway in low carbon emission blast furnace. (8th April 2023) - Ren, Mengmeng; Liu, Wenwen; Zhao, Junxue; Zou, Chong; Ren, Lei; Wu, Hao; Zhao, Jun
Abstract: Co-injection of coal and hydrogen-rich gas with oxygen blast at tuyere is a promising technology for low carbon emission blast furnace ironmaking, which favors the development of hydrogen-based reduction and affordable carbon capture. Effects of hydrogen fraction in the co-injection gas on the combustion characteristics in raceway are numerically studied. Results show that increase of hydrogen fraction in the co-injection gas accelerates the preferential combustion of the injected gas, which promotes the preheating and pyrolysis of pulverized coal. This compensates the oxygen-grabbing effect and improves the burnout of coal from 83.2% to 86.8% with the hydrogen fraction in co-injection gas increase from 20 vol% to 80 vol%. With the CO/H2 molar ratios in the co-injection gas of 8:2, 6:4, 4:6 and 2:8, the outlet CO/H2 molar ratios are 54:46, 42:52, 32:68 and 24:76 respectively. Combustion, gasification and water-gas shift reactions play conjoint roles in the redistribution of reducing gas species. Highlights: EDC model is applied to consider gaseous reaction equilibrium. The prediction accuracy of temperature fields is improved. Increase of hydrogen fraction promotes the pulverized coal burnout. Heat-release effect and oxygen-grabbing effect of gas preferential combustion are evaluated.